2011
DOI: 10.1016/j.molcel.2011.09.026
|View full text |Cite
|
Sign up to set email alerts
|

p50 (NF-κB1) Is an Effector Protein in the Cytotoxic Response to DNA Methylation Damage

Abstract: SUMMARY The functional significance of the signaling pathway induced by O6-methylguanine (O6-MeG) lesions is poorly understood. Here, we identify the p50 subunit of NF-κB as a central target in the response to O6-MeG and demonstrate that p50 is required for SN1-methylator-induced cytotoxicity. In response to SN1-methylation, p50 facilitates the inhibition of NF-κB-regulated anti-apoptotic gene expression. Inhibition of NF-κB activity is noted to be an S-phase specific phenomenon that requires the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(127 citation statements)
references
References 27 publications
13
111
1
2
Order By: Relevance
“…S2A). It is possible that this transient activation reflected an interaction of MMR with the checkpoint machinery as observed previously both in vitro [17,18] and in vivo [19,29].…”
Section: Resultsmentioning
confidence: 52%
“…S2A). It is possible that this transient activation reflected an interaction of MMR with the checkpoint machinery as observed previously both in vitro [17,18] and in vivo [19,29].…”
Section: Resultsmentioning
confidence: 52%
“…While all NF-κB subunits contain a conserved N-terminal rel homology domain (RHD), only p65, relB and crel have a C-terminal transactivation domain (TAD). p50 is a ubiquitously expressed NF-κB subunit that is targeted by the temozolomide-induced DNA damage response (8). Despite the lack of a TAD, p50 can induce NF-κB-dependent gene expression by associating with other rel subunits or co-regulator proteins.…”
Section: Introductionmentioning
confidence: 99%
“…DNA replication stress results in the activation of the checkpoint kinases ATR and Chk1. Building on previous work from the Yamini group demonstrating that Chk1 can phosphorylate p50 at serine 329, 3 here it is shown that this modification is required for NF-kB dependent cell death following DNA replication stress. 1 This effect, which is associated with down regulation of anti-apoptotic genes such as Bcl-xL, is lost in NF-kB1 null cells reconstituted with S329 mutant forms of p50.…”
mentioning
confidence: 52%